"Like sheep for the slaughter": An investigation of Luther's concept of larva Dei and the vocation of the soldier in relation to Foucault's interpretation of the pastorate. (2nd January 2016) - Yngvesson, Susanne Wigorts
Abstract : The primary objective of this article is to investigate how a Lutheran theology supports the soldier's vocation in war. First, the analysis is made in relation to the concept of larva Dei, second, in relation to "the pastorate" and "technology of power". By the interaction, I show how Luther's theology can be used as a critique towards Foucault and vice versa. Through this narrative method, structures of power and liberation are unveiled. The interaction illuminates their diverse views on secular and non-secular order, as well as an immanent and transcendental order. Luther points towards eternity, while Foucault points towards society and its powers. The main outcome is firstly: faith for Foucault is never an explanation of "reality", but a result of social relations. For Luther, faith is to experience the world as reality; and secondly: larva Dei creates a possibility to overcome suffering by faith, whereas by Foucault's immanent structure, suffering is understood as "empty" or "meaningless". Foucault contributes with an important critique of misusing vocation in war. An area for further research is to continue developing critiques of vocation and power in relation to contemporary soldiers', terrorists' and anarchists' masks, since some are used to protect life and others to protect identities.